Masyarakat Mantap - Qurotul Aini, Siti Maryam; Sukandar, Sukandar; Umami, Hafidul (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
The role and function of the mosque in rural Takmir often still dwell on the management and service, has not touched on the empowerment efforts of pilgrims. Takmir Mosque has the opportunity to develop community based education. In this case the role of the college in the mentoring of the mosque Takmir indispensable. This mentoring uses an ABCD (asset based community Development) approach conducted in Jatipunggur Lengkong Nganjuk village. The result of mentoring managed to realize community based education in the form of empowering the mosque Takmir to build worshippers in terms of the care of the body and to overcome femininity problems. This achievement can be achieved because the process of mentoring from the stage of social analysis, planning, implementation and evaluation is done with all the mosque stakeholders. Takmir Mosque managed to get mentoring to organize community based education by involving administrators, village apparatus and religious and community leaders.